2019
DOI: 10.21873/anticanres.13358
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma Induces HMGB1 Expression in Cancer Cells

Abstract: Background/Aim: Plasma medicine is a new field that provides great potential for the treatment of human diseases including cancer in addition to sterilizing the surface of skin and facilitating wound healing. Recently, nonthermal atmospheric plasma (or cold atmospheric plasma, CAP) was introduced, not only for denaturing cells and tissues, but also for operating under the threshold of thermal damage and for chemically inducing a specific response or modification. Materials and Methods: Microwave-mediated CAP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In this way, PAM rich in H 2 O 2 was shown to increase calreticulin exposure and ATP release in tumour cells [117]. CAP exposure induced cell death of MX-7 rhabdomyosarcoma cells [118] and of vestibular schwannoma cancer cells [119] via similar calreticulin and HSP70 externalization and increased HMGB1 release. Prostate cancer cells exposure to CAP-PBS resulted in their enhanced immunostimulatory secretion profile (higher TNF-α and IFN-γ, lower TGF-β), and increased phagocytosis by dendritic cells [17], whereas in CAP-exposed keratinocytes, expression of key regulators important for inflammation (IL-8, TGF-β1, and TGF-β2) was found increased [120].…”
Section: Immune Response Activating Cell Deathmentioning
confidence: 86%
“…In this way, PAM rich in H 2 O 2 was shown to increase calreticulin exposure and ATP release in tumour cells [117]. CAP exposure induced cell death of MX-7 rhabdomyosarcoma cells [118] and of vestibular schwannoma cancer cells [119] via similar calreticulin and HSP70 externalization and increased HMGB1 release. Prostate cancer cells exposure to CAP-PBS resulted in their enhanced immunostimulatory secretion profile (higher TNF-α and IFN-γ, lower TGF-β), and increased phagocytosis by dendritic cells [17], whereas in CAP-exposed keratinocytes, expression of key regulators important for inflammation (IL-8, TGF-β1, and TGF-β2) was found increased [120].…”
Section: Immune Response Activating Cell Deathmentioning
confidence: 86%
“…For CAP activity, it was verified that the CAP treatment of B16F10 cells promoted DC maturation in vitro [ 2 ]. In addition, Yoon and co-authors have also shown that CAP induced the expression of HMGB1 in cancer cells [ 11 ]. These findings indicated that CAP can change the intra- and extra-cellular level of HMGB1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts focused on detecting and identifying the basic processes of plasma had an aim of designing plasma machines for specific applications. Although most studies focused on dielectric-barrier discharge (DBD) methods, we recently reported the use of microwave plasma to induce immunogenic cell death in human cancer cells [ 6 ]. Cold atmospheric plasma (CAP) is ionized gas with high energy at relatively low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma medicine recently became a new area in human medicine [ 10 ] due to its mechanisms—including DNA damage, apoptosis, necrosis or autophagy by stimulating many ROS-mediated signaling pathways—leading to anticancer activity [ 11 , 12 , 13 ]. Recent studies have demonstrated that plasma can induce immunogenic cell death in cancer cells, which provides a potential application in cancer immunotherapy [ 6 , 14 , 15 ]. The use of CAP for biomedical treatments is an exciting new application, and could take plasma further in systematic medical research.…”
Section: Introductionmentioning
confidence: 99%